2020
DOI: 10.1113/jp279605
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric mapping of the functional neuroanatomy of the respiratory network in the perfused brainstem preparation of rats

Abstract: Key points The functional neuroanatomy of the mammalian respiratory network is far from being understood since experimental tools that measure neural activity across this brainstem‐wide circuit are lacking. Here, we use silicon multi‐electrode arrays to record respiratory local field potentials (rLFPs) from 196–364 electrode sites within 8–10 mm3 of brainstem tissue in single arterially perfused brainstem preparations with respect to the ongoing respiratory motor pattern of inspiration (I), post‐inspiration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…Readiness potential amplitudes were also smaller during the expiration phase as compared to inspiration. This interpretation of the results is further supported by a recent study of Dhingra et al (2020) showing that the transitions between inspiration and post-inspiration are especially relevant for synaptic engagement: the I-PI transition exclusively engages a brainstem-wide respiratory network.…”
Section: Breathing In: Brain-body Interactionssupporting
confidence: 79%
“…Readiness potential amplitudes were also smaller during the expiration phase as compared to inspiration. This interpretation of the results is further supported by a recent study of Dhingra et al (2020) showing that the transitions between inspiration and post-inspiration are especially relevant for synaptic engagement: the I-PI transition exclusively engages a brainstem-wide respiratory network.…”
Section: Breathing In: Brain-body Interactionssupporting
confidence: 79%
“…In fact, late-inspiratory and postinspiratory dorsolateral pontine neuronal activity always occurred in the three-phase output and never occurred during shallow two-phase respiratory output. This finding suggests pontine neuronal activity is correlated with three-phase breathing (defined by postinspiratory vagal output and augmenting phrenic output), which is highly congruent with the role of the dorsolateral pons in the inspiratory off-switch ( 17 , 19 , 20 , 37 40 ), and the loss of decrementing vagal postinspiratory activity and augmenting phrenic inspiratory activity following opioid administration into the dorsolateral pons ( 11 ).…”
Section: Discussionmentioning
confidence: 54%
“…Recently, we have demonstrated that balanced excitation and inhibition within the ventrolateral respiratory column, dorsal respiratory group and pontine respiratory group is necessary for the expression of the three-phase respiratory motor pattern ( Dhingra et al., 2019a ). Further, by mapping the distribution of local field potentials throughout a broad region of the medulla and pons that contain the core elements of the respiratory network, we were able to demonstrate that the transition from inspiration to postinspiration simultaneously engaged an expansive network that includes the ventrolateral respiratory column, dorsal and pontine respiratory groups ( Dhingra et al., 2020 ). Further, the formation of the respiratory motor pattern depends on synaptic interactions between the medullary ventrolateral respiratory column and the pontine respiratory groups ( Jones and Dutschmann, 2016 ).…”
Section: Introductionmentioning
confidence: 95%